ANALISIS MANAJEMEN SIKLUS OBAT ANTIHIPERTENSI DAN DAMPAKNYA TERHADAP KETERSEDIAAN DI INSTALASI FARMASI RAWAT JALAN RSU AT MEDIKA - Muhammad Irvan Akbar Nur; Ahmad Najib; Audia Triani Ollii (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The implementation of National Health Insurance mandates hospitals to ensure the availability of essential medicines, yet recurring antihypertensive drug stockouts persist at RSU AT Medika. This study examines drug cycle management implementation, its impact on availability, and the influencing factors. Employing a descriptive qualitative approach with a single case study design, data were collected through in-depth interviews with 7 pharmacy informants and 15 hypertensive patients who had experienced stockouts, participatory observation, and document review from January to December 2025. Thematic analysis with data saturation and source triangulation was applied, assisted by NVivo software. The findings reveal that formal procedures have been executed according to standards, yet significant gaps exist between administrative compliance and operational reality. Planning based on historical data frequently proves inaccurate due to patient surges, while procurement through the hierarchical e-Catalog system constitutes the primary source of delays due to stock discrepancies. Stockout has been normalized as commonplace, disrupting patient therapy, burdening staff psychologically, and posing medico-legal risks. JKN regulation through e-Catalog presents a paradox: suppressing prices while hindering availability. The study concludes that antihypertensive drug availability is not merely logistical, but concerns patient safety and JKN system effectiveness.